Helping the Singapore arts sector survive the Covid-19 crisis - HOE, Su Fern (Institutional Knowledge at Singapore Management University, 2020)
From online art classes to livestreaming performances and collective singing to cheer frontline healthcare workers, people across the globe are turning to the arts for much-needed connection and comfort amid the Covid-19 crisis.